Role of B-cells in Mycosis Fungoides - Pia Rude Nielsen; Jens Ole Eriksen; Mia Dahl Sørensen; Ulrike Wehkamp; Lise M. Lindahl; Michael Bzorek; Lars Iversen; Anders Woetman; Niels Ødum; Thomas Litman; Lise Mette Rahbek Gjerdrum (Medical Journals Sweden, 2021)
Mycosis fungoides is the most common type of cutaneous T-cell lymphoma. The inflammatory microenvironment in mycosis fungoides is complex. There is accumulating evidence that the neoplastic T-cells take control of the microenvironment and thereby promote their own expansion by suppressing cellular immunity. B-cells have proved to be upregulated in large-cell transformed mycosis fungoides, and could potentially play a role in disease progression. To investigate the presence of B-cells in mycosis fungoides compared with controls, this study analysed 85 formalin-fixed and paraffin-embedded mycosis fungoides biopsies. MS4A1 gene expression was significantly upregulated in mycosis fungoides compared with controls (p < 0.0001) and further upregulated in disease progression, (p = 0.001). Digital quantification of PAX5+/CD20+ cells confirmed the increased presence of B-cells in mycosis fungoides compared with controls. No co-labelling of CD3/CD20 was observed in the neoplastic T-cells. This study found a significantly increased presence of B-cells in the tumour-associated microenvironment in mycosis fungoides. These findings could potentially lead to new treatment strategies for mycosis fungoides.